Electrical Resistivity Tomography as a Geotechnical Justification Support (Case Study Makassar – Pare-Pare Railway Bed Construction KM 68+450 to KM 68+750) - Sasmayaputra, Nur Alfian; Wibowo, Dian Eksana; Fajarwati, Yuli; Endaryanta, Endaryanta; Aswad, Sabrianto; Widiastuti, Nur Oktaviani (INERSIA lnformasi dan Ekspose Hasil Riset Teknik Sipil dan Arsitektur, 2024)
This study examined the presence of underground water channels under the Makassar - Pare-pare railway line KM 68+450 – KM 68+750 and the design concept for the technical solution. The potential for underground water channels was identified during construction, based on community information, the location's morphological phenomena, and  geological conditions whose base rock was the limestone formation. The problems can cause instability of the railway line, resulting in unsafe train travel. One of the characteristics of limestone rock conditions is its hollow shape, like a cave that can become underground water flow. It was a case study whose solution was based on data obtained from geotechnical investigations. Boring testing can only provide information on soil layers at the test point and cannot describe soil stratigraphy section, including underground water channel.  Combination  ERT and Boring tests were carried out to examine the presence of underground water channels. This study was conducted in three stages: initial identification, advanced identification, and design concept of Technical Solution. In these three stages, data collection and analysis were carried out. The results of the study indicated that ERT tests could provide a picture of the subsurface to shallow bedrock, thus facilitating the justification of geotechnical design. From the analysis, it was concluded that no channel cavities, such as caves, that function as underground water channels. The existing water flow was estimated to be a confining aquifer where water flows due to the height difference in the surrounding morphological conditions through the media of the broken limestone water shaft. It was confirmed with the results of Boring and ERT tests. The proposed technical solution concept was strengthening the Dolken embankment structure and geogrid, combined with a subdrain layer. The technical solution was prepared based on the results of research on construction contract data and project resource readiness.